The Effect Of Product Quality And Brand Image On Customer Loyalty In Skintific Products (Case Study On Gen Z In Palu City) - Nova Anggriani; Zakiyah Zahara; Maskuri Sutomo; Pricylia Chintya Dewi Buntuang (UNIVED Press, 2025)
The purpose of this study was to determine and analyze: (1) the effect of product quality and brand image on customer loyalty on skintific products in Palu city, (2) the effect of product quality on customer loyalty on skintific products in Palu city, (3) the effect of brand image on customer loyalty on skintific products in Palu city. The type of research used is quantitative (shows the relationship between variables). The population in this study were gen Z customers in Palu city who used skintific products. The sampling technique in this study used purposive sampling, with a total sample size of 110 respondents. Data collection using a questionnaire. The analysis method used is multiple linear regression analysis using the SPSS release 26 application. The results showed that (1) there is an effect of product quality and brand image on customer loyalty on skintific products in the Palu city (2) there is an effect of product quality on customer loyalty on skintific products in the Palu city (3) there is an effect of brand image on customer loyalty in the Palu city.